Population structure, fecundity and morphological characteristics of M. vollenhovenii (Herklots, 1857) on lower volta river basin channel, Ghana - Eniade Abiodun, Adeyemi; Odedeyi Dominic, Olabode; Bello-Olusoji A, Oluayo; Adebayo Olabode, Thomas; Agyakwah Seth, Koranteng (African Journal of Biological Sciences, 2019)
Population structure, fecundity and morphological characteristics of M. vollenhovenii were studied around Lower Volta River, Ghana subject to dirt of information on this prawn species around the study location. The most prominent morphological characteristics already documented for identification of this species was rostrum bearing 13-15 continuous teeth dorsally and 4-5 teeth on its ventral part. These morphological traits formed the principal components for identification in this study. Results showed that morphological traits on second pereiopods such as presence of spines, spinules, teeth borne within the fingers, and dense projections of setae-like features on telson and uropod were observed relevant for identification purposes. Other results revealed that maximum total length recorded in this study (150-155mm) was higher than total length ranges (≤125mm) documented for this species in earlier studies. Consequently, two adult’s classes of prawns were identified (old adult class 81-120mm; and young adults 31-80mm) and older class was observed to be more in catches than the younger prawns. Absolute fecundity revealed that oocytes estimation varied with respect to seasons, ages of prawns and body sizes of specimens examined. In conclusion, this study observed that M. vollenhovenii fishery is operating in a sustainable manner at the time of this study around the study location.
Keywords: Lower Volta River, M. vollenhovenii, Population structures, Absolute fecundity, Morphometric Characters